A Survey of Sleep Quality From a Post-COVID Clinic - Mantavya Punj; Michael Schwartz; Anjali Morris; Joseph Cheung; Bala Munipalli (SAGE Publishing, 2024)
Objectives: To assess the prevalence of sleep disturbance among patients evaluated at a clinic for patients afflicted with Post-acute sequelae of COVID-19 (PASC). Methods: Sleep disturbance was assessed with the Patient-Reported Outcomes Measurement Information System-Sleep Disturbance (PROMIS-SD) framework among adult patients of the PASC clinic. Results: Among 312 patients, the mean age was 46.2 years, and 70.2% were women. About 41.0% of patients had no sleep disturbance; sleep disturbance was mild to moderate in 51.3% and severe in 7.7%. PROMIS-SD score was negatively correlated with the time from the initial positive COVID-19 test to the initial consultation in the PASC clinic (Pearson r  = −.094; r 2  = .0088). Conclusions: The PROMIS-Sleep Disturbance framework can serve as a tool to assess the burden of sleep disturbances in PASC patients.